In the Blink of An Eye : A Perspective on Film Editing 2nd Edition - Walter Murch (Los Angeles, CA, United States Silman-James Press,U.S., 2001)
d
Keywords: Group-6 - Visual Arts / Films -- Group-6 - Visual Arts / Films